ҚАРАҚАЛПАҚ ФОЛЬКЛОРЫНДА АНА ҲӘМ БАЛА ОБРАЗЫ - Жақсылықова, А.; Бекбергенова, М. (FAN va JAMIYAT, 2016)
The article deals with the educational role of Karakalpak folklore on the basis of the analysis of fairy-tales, proverbs and sayings in which the relations between mother and child, good and bad are expressed. Folklore plays an important role in the education of young generation.